Eksperimen Model Pembelajaran Numbered Head Together (Nht) Berbasis Penilaian Portofolio Terhadap Hasil Belajar Matematika Ditinjau Dari Ketrampilan Pemecahan Masalah Siswa Kelas Vii Madrasah Tsanawiyah Negeri Tinawas Tahun Ajaran 2016/2017 - Putri Ratnasari, Lintang, Muhammad Noor Kholid, M.Pd (2017)
Abstarct The aim of this research is to analyze: (1) the detect of implementation influence of Numbered Head Together (NHT) model based on portfolio assessment, Numbered Head Together (NHT), and Expository to mathematics learning outcome, (2) the detect of students' problem-solving skill to the mathematics learning outcome, (3) the detect of interaction between the application of the three learning models to the level of problem-solving skill to the mathematics learning outcome. This research is a quantitative research with quasi-experimental research design. The population in this research is all students of class VII MTs Negri Tinawas 2016/2017. The sampling technique in this study used cluster random sampling. The methods in collecting data are documentation, questionnaire, and learning test result. The analysis data technique is using two ways variation analysis with different cell. The results of the analysis with significance level of 0.05 indicate that: (1) there is a difference of influence of Numbered Head Together (NHT) based learning model based on portfolio assessment, Numbered Head Together (NHT), and Expository on mathematics learning result with FA = 9,4419 (2 ) There is difference of influence of level of problem solving skill of student to result of learning of mathematics with FB = 31,6819 (3) there is no interaction between three model of learning with level of problem solving skill of student to result of learning mathematics with FAB = 0,0081. For implications for teachers, teachers need to pay attention to problem solving skills because the results show the problem solving skills affect the student's mathematics learning outcomes. Keywords: Portfolio Assessment, Numbered Head Together (NHT), problem solving skills, mathematics learning outcomes.